On the numerical investigations to the Cahn-Allen equation by using finite difference method - Yokuş, Asıf; Bulut, Hasan (Balikesir University, 2019)
In this study, by using the finite difference method (FDM for short) and operators, the discretized Cahn-Allen equation is obtained. New initial condition for the Cahn-Allen equation is introduced, considering the analytical solution given in Application of the modified exponential function method to the Cahn-Allen equation, AIP Conference Proceedings 1798, 020033 [1]. It is shown that the FDM is stable for the usage of the Fourier-Von Neumann technique. Accuracy of the method is analyzed in terms of the errors inL 2 andL Furthermore, the FDM is treated in order to obtain the numerical results and to construct a table including numerical and exact solutions as well as absolute measuring error. A comparison between the numerical and the exact solutions is supported with two and three dimensional graphics via Wolfram Mathematica 11. © 2019 Balikesir University. All rights reserved.
Keywords: Cahn-Allen equation Finite Difference Method Numerical Solution